Characterization of the complete plastome of Thalictrum aquilegiifolium var. sibiricum (Ranunculaceae), an annual herb - Rui Wang; Bo-Qiang Tong; Xin-Yan Yang; Xue-Jie Zhang (Mitochondrial DNA. Part B. Resources, 2022)
Thalictrum aquilegiifolium var. sibiricum, is an annual herb that grows on slopes or in mountain gullies in areas of damp forest. In this study, we report for the first time the complete plastome sequence of T. aquilegiifolium var. sibiricum. The plastome sequence is 156,244 bp in length and comprises a large single-copy region (85,447 bp), a small single-copy region (17,599 bp), and a pair of inverted repeat regions (26,480 bp). The genome encodes 112 unique genes, including 78 protein-coding genes, 30 tRNAs, and four rRNAs, and has total GC content of 38.4%. Phylogenomic analysis based on the plastome sequences of 20 species in the family Ranunculaceae indicated that T. aquilegiifolium var. sibiricum is clustered with Thalictrum minus.